Llama (Lama glama) semen collection via thermo-electric artificial vagina: effect of seasonality and collection interval on ejaculate characteristics - Ferre, Luis Bernardo (2015)
Adult male Llamas (Lama glama) (n = 6) were collected using a receptive female and a thermo-electric artificial vagina assembled with a polyethylene collection bag with the following objectives: (a) to develop a reliable and repeatable semen collection technique for Llama, (b) validate semen evaluation tests for Llama, and (c) to determine the effect of collection frequency and season on Llama semen characteristics. First, the semen and sperm variables were recorded and validated through their own repeatability. Semen collection intervals tested were: 1X/week for three weeks and 3X/week for another three weeks, the second collection period occurring after two weeks of sexual rest. The collection frequency of 3X/week significantly reduced (P < 0.05) the sperm viability, motility, concentration, Total Sperm/Ejaculate, Total Motile Sperm/Ejaculate and Total Live Sperm/Ejaculate, but improved Total Sperm/Week and Total Live Sperm/Week. All recorded variables were significantly higher during the summer in comparison to the spring with the exception of morphology abnormalities, volume, and viability. Also, the 1X/week versus the 3X/week semen collection frequencies did not produce a significant difference in the percent of total motile sperm/week. Based on semen and sperm characteristics evaluated herein, Llama semen collected in the summer was better (P < 0.05), with regard to the majority of the variables analyzed, than semen collected in the spring.